Persepsi Pasien terhadap Efektivitas Program Jaminan Kesehatan Nasional (JKN) di Rumah Sakit Hikmah Citra Medika Sengkang: Studi Kualitatif - A. Nur Azizah; Idarwati Mustafa (Journal Research of Health Administration and Public Health (JRHAPH), 2025)
Achieving Universal Health Coverage (UHC) through the Jaminan Kesehatan Nasional (JKN) program is a priority of the Indonesian government to ensure affordable access to healthcare services. Although membership coverage has increased significantly, evaluation based on patients’ real experiences remains crucial to identify implementation barriers in practice. This study aimed to explore patients’ perceptions of the effectiveness of the JKN program at RS Hikmah Citra MedikaSengkang. This study employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews with 15 BPJS Kesehatan patients who were hospitalized in October 2025 at RS Hikmah Citra Medika. Participants were selected using purposive sampling, and data analysis was conducted using the Paul Colaizzi method. The analysis generated five main themes: (1) improved healthcare accessibility despite waiting time constraints; (2) significant financial protection, although out-of-pocket expenses were still reported for non-medical needs or certain medications; (3) responsive and patient-centered medical service quality; (4) administrative procedures perceived as clear yet complex, particularly in referral pathways; and (5) perceptions of equitable care in medical treatment but differences in supporting facilities. Overall, the JKN program at RS Hikmah Citra Medika was perceived positively in terms of access and financial protection. However, program effectiveness remains limited by administrative barriers, waiting times, and perceived disparities in facility equity. These findings indicate the need for systemic improvements, particularly in simplifying bureaucratic processes and aligning service standards to ensure the realization of social justice principles for all participants.